(untitled) (Fiep Bulletin - online, 2013)
The present study investigates meanings conferred by a Physical Education teacher to the democratic management of a school whose proposition is innovative. The theoretical reference used was the sociology of school organization (BALL, 1989). The Law on Education Guidelines and Basis (LDB), no. 9.394/96, characterizes Physical Education as an obligatory curricular component of basic education, integrates it to the pedagogical proposition of schools, and gives teachers the responsibility of this articulation within the framework of the management of the Political Pedagogical Project of each school unit. By means of a qualitative case study, we identified a school locus in the context of a municipal school network. In the school studied, courses count with isonomy of their working hours, and activities are developed in thematic classrooms. The participating teacher is the only Physical Education teacher of the school. The investigation was conducted by means of a semi-structured interview, document analysis, and observation. Results show that innovations do not interfere with the teaching-learning process in the area of Physical Education, since the knowledge that bases the teacher’s concepts comes from previous experiences, forged in a meritocratic view. There was a divergence between the concept of school Physical Education understood by the teacher and the political pedagogical principles that structure the school. The spaces for discussion made available by the school were undervalued by the teacher because he does not identify them as relevant in order to resignify his practice. Built under this aegis, school Physical Education reinforces the marginality of the course and does not confer it the centrality that the political pedagogical project intends to realize.